A Note on Isomorphism Theorems for Semigroups of Order-Preserving Transformations with Restricted Range - Phichet Jitjankarn; Thitarie Rungratgasame (International Journal of Mathematics and Mathematical Sciences)
Finding necessary and sufficient conditions for isomorphism between two semigroups of order-preserving transformations over an infinite domain with restricted range was an open problem. In this paper, we show a proof strategy to answer that question.